Exploration and Morphological Character Identification of Local Durian (Durio zibethinus Murr.) from Tidore Island, North Maluku - Sundari, Sundari; Arumingtyas, Estri Laras; Hakim, Luchman; Azrianingsih, Rodiyati (Proceeding International Conference on Global Resource Conservation, 2015)
Local durian is the name for Durio zibethinus Murr. found in the Tidore Island, North Maluku. There are many local names for local durian in Tidore Island that have many different morphological variation. The objective of this study was to inventarize and analyze the morphological charactervariations of 19 local durian names collected from 9 villages: Gurabunga, Gubukusuma, Afa-afa, Fobaharu, Foralaha, Jaya, Bobo, Dokiri and Rum in the Tidore Island, North Maluku. This research was conducted in March-June 2015 using descriptive exploratory method with purposive sampling. Local durians found in Tidore Island have variations local names and variation of morphological characters include: habitus, leaf shape, fruit shape, flesh color and texture, seedshape, and the shape ofthe aril thorn.Â Keywords: inventarization; local durian; morphological characters; Tidore Islands